Coronavirus COVID-19 outbreak & Dentistry; Routes of Transmission & Infection- Control Challenges and Responsibilities - Raafat. Tammam; Amr Mohamed Ibrahim (Institute of Medico-legal Publications Pvt Ltd, 2021)
The 2019 coronavirus disease (COVID-19) pandemic, originating in Wuhan, China, is becoming a majorpublic health problem for not only China, but countries all over the world as well. The World HealthOrganization (WHO) has reported that outbreaks of the novel coronavirus have become a globally worriedpublic health emergency. As of February 4, 2021, COVID-19 has been recognized in 235 countries, withmore than 105.000.000 (one hundred and five millions) laboratory-confirmed cases and above 2.280.000(million) deaths. To prevent the virus from further spreading and to help manage the disease situation,infection control measures are necessary. The risk of cross contamination can be high between patients anddental practitioners because of the characteristics of dental settings. Strict and efficient infection managementprotocols are urgently needed for dental practices and hospitals in areas which are (potentially) affected byCOVID-19. This article, based on our experience and relevant guidelines and research, introduces essentialknowledge about COVID-19 and nosocomial infection in dental settings and provides recommendedmanagement protocols for dental practitioners and students in (potentially) affected areas.